Microresonator soliton frequency combs via cascaded Brillouin scattering - Zhang, Hao; Zhang, Shuangyou; Bi, Toby; Ghalanos, George; Zhang, Yaojing; Yan, Haochen; Pal, Arghadeep; He, Jijun; Pan, Shilong; Del’Haye, Pascal (Communications Physics, 2025)
Microresonator frequency combs are vital for advancing optical communications and sensing, but current methods face challenges in achieving low phase noise and flexible repetition rates simultaneously. Here, we demonstrate forward-propagating soliton frequency combs using cascaded Brillouin scattering in a silica resonator. This method bridges distinct resonator modes and decouples soliton repetition rates from the Brillouin frequency shift ( 10 GHz in silica). By generating soliton pulses at 107 GHz, we show that the repetition rates can be tailored through resonator geometry without compromising low noise. This integration of Brillouin lasing with microcombs unites stability and design flexibility, overcoming prior limitations. The results can enable scalable photonic platforms for applications such as LiDAR, high-capacity optical networks, and precision microwave generation. This technique is of interest for technologies that demand both ultra-stable and customizable light sources.
CRIS-Team Scopus Importer:2025-05-30